IMPLEMENTASI SISTEM LAPORAN KEUANGAN DAN PERHITUNGAN PPH FINAL BERBASIS MICROSOFT EXCEL SEBAGAI UPAYA PENENTUAN LABA PADA UMKM KUE MAMA FADIL - Pemas Hamonangan Sinaga; Johandri Iqbal; Ivan Ramadhan (LP2M Politeknik Jambi, 2026)
This study aims to implement a Microsoft Excel–based financial reporting system and Final Income Tax (PPh Final) calculation as an effort to determine profit at UMKM Kue Mama Fadil. The main problems identified include manual financial recording, non-compliance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM), and the absence of Final Income Tax calculation in accordance with Government Regulation Number 55 of 2022. This research applies an applied research method with a descriptive qualitative approach through observation, interviews, and documentation. The results indicate that the implementation of a Microsoft Excel–based financial reporting system enables the UMKM to record transactions systematically, prepare financial statements in accordance with SAK EMKM, determine business profit more accurately, and calculate Final Income Tax automatically and in an integrated manner. The system also improves the owner’s understanding of the business’s financial condition and tax obligations. Therefore, the Microsoft Excel–based financial reporting and Final Income Tax calculation system is considered effective and sustainable in supporting UMKM financial management. Keywords: MSMEs, Financial Statements, Final Income Tax.